(untitled) (Ustozlar uchun, 2024)
Key words: Linguistic-cultural analysis, Happiness, English language, Uzbek language, Semantic range, Cultural nuances, Subjective experiences, Lexical items, Idiomatic expressions, Well-being, Cultural attitudes, Language and culture, Cross-cultural comparison, Emotion vocabulary, Cultural diversity.